144k views
3 votes
Which value for s will make this equation true ?

Which value for s will make this equation true ?-example-1

1 Answer

7 votes

The given equation is

s(11 - s) = 24

We can expand the bracket by multiplying each term inside the bracket by the term outside.

It becomes

11s - s^2 = 24

- s^2 + 11s - 24 = 0

Multiplying through by - 1, it becomes

s^2 - 11s + 24 = 0

We would factorise by finding two numbers whose sum or difference is - 11s and whose product is 24s^2. The numbers are - 8s and - 3s

Therefore, the equation becomes

s^2 - 8s - 3s + 24 = 0

s(s - 8) - 3(s - 8) = 0

(s - 8)(

User Abhishek Choubey
by
5.4k points